2013
DOI: 10.1007/s00737-013-0348-9
|View full text |Cite
|
Sign up to set email alerts
|

Does breastfeeding offer protection against maternal depressive symptomatology?

Abstract: Mothers who breastfeed typically exhibit lower levels of depressive symptomatology than mothers who do not. However, very few studies have investigated the directionality of this relationship. Of the prospective studies published, all but one focus exclusively on whether maternal depression reduces rates of subsequent breastfeeding. This study again examines this relationship, but also the reverse—that breastfeeding might predict lower levels of later depression. Using multilevel modeling, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 65 publications
(85 reference statements)
4
92
0
2
Order By: Relevance
“…However, Gaillard et al (2014) did not report similar finding. Other factors, such as lack or non-initiation of breastfeeding (Chien et al, 2006;Green et al, 2006;Mosack and Shore, 2006;Lau and Chan, 2007;Baker and Oswalt, 2008;Davey et al, 2011;Sword et al, 2011;Watkins et al, 2011;Figueiredo et al, 2013;Hahn-Holbrook et al, 2013), parity (Green et al, 2006;Glavin et al, 2009;Hamdan and Tamim, 2011;Kozinszky et al, 2011;Sword et al, 2011;Raisanen et al, 2013;Gaillard et al, 2014) and sex of baby (Boyce and Hickey, 2005;de Tychey et al, 2008;Kim et al, 2008;Koutra et al, 2014) showed mixed findings. Women whose infants had medical illnesses (Green et al, 2006;Ueda et al, 2006;Kim et al, 2008;Raisanen et al, 2013), are born prematurely (Raisanen et al, 2013) and are temperamentally difficult (McGrath et al, 2008;Eastwood et al, 2012) are likely to experience postpartum depression.…”
Section: Obstetric and Pediatric Factorsmentioning
confidence: 79%
“…However, Gaillard et al (2014) did not report similar finding. Other factors, such as lack or non-initiation of breastfeeding (Chien et al, 2006;Green et al, 2006;Mosack and Shore, 2006;Lau and Chan, 2007;Baker and Oswalt, 2008;Davey et al, 2011;Sword et al, 2011;Watkins et al, 2011;Figueiredo et al, 2013;Hahn-Holbrook et al, 2013), parity (Green et al, 2006;Glavin et al, 2009;Hamdan and Tamim, 2011;Kozinszky et al, 2011;Sword et al, 2011;Raisanen et al, 2013;Gaillard et al, 2014) and sex of baby (Boyce and Hickey, 2005;de Tychey et al, 2008;Kim et al, 2008;Koutra et al, 2014) showed mixed findings. Women whose infants had medical illnesses (Green et al, 2006;Ueda et al, 2006;Kim et al, 2008;Raisanen et al, 2013), are born prematurely (Raisanen et al, 2013) and are temperamentally difficult (McGrath et al, 2008;Eastwood et al, 2012) are likely to experience postpartum depression.…”
Section: Obstetric and Pediatric Factorsmentioning
confidence: 79%
“…We also found higher rates of perceived lactation dysfunction among women with postpartum-depression symptoms. Postpartum depression is associated with reduced breastfeeding duration, 15,16,[33][34][35][36] and neuroendocrine mechanisms may underlie this association. 12,21 Moreover, reduced maternal sensitivity 37 in the setting of depression may also contribute to breastfeeding difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…This finding also adds complexity to ongoing research regarding the potential protective role of breastfeeding against PP depression. 9 In addition to the hypothesized roles of infant bonding and hormonal response, these findings suggest a possible socialcognitive influence as well. Some women may view breastfeeding as an early sign of success or failure in the role of motherhood, and how a woman feels she is doing at this task may be important in shaping her early PP emotional experience.…”
Section: Breastfeeding Self-efficacy and Moodmentioning
confidence: 94%